METODE ANALISIS REGRESI SPASIAL DALAM MEMODELKAN KASUS COVID-19 DI INDONESIA - PUSPASARI, NI MADE; SUCIPTAWATI, NI LUH PUTU; SUSILAWATI, MADE (E-Jurnal Matematika; Vol 11 No 3 (2022), 2022)
Covid-19 is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2. The transmission of Covid-19 has negative impact on every aspect. This study aimed  to determine the factors that significantly affect the number of Covid-19 cases in Indonesia. Spatial regression analysis was used as the research method. The results obtained that on the dependent variable there is a spatial dependence, so the selected model is Spatial Autoregressive Model (SAR) with an AIC value of 759.09 and an  value of 58.49%. The significant influencing factor is proportion of the population over 50 years old and open unemployment rate.